1981
DOI: 10.1088/0022-3727/14/7/001
|View full text |Cite
|
Sign up to set email alerts
|

Free convection flow through a porous medium bounded by a vertical surface

Abstract: Steady two-dimensional free convection flow through a porous medium bounded by a vertical infinite surface is considered. Expressions for the velocity, temperature and the rate of heat transfer are obtained. Effects of G (Grashof number) and K (permeability parameter) on the velocity and the rate of heat transfer are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 4 publications
0
35
0
Order By: Relevance
“…Figure 1 gives the variation of f along with the distance from the plate. The variation of 1 A , the parameter which is associated with the viscosity function of the temperature produce a substantial change in a single valued function f of  . It is observed that the values of f increases sharply in magnitude as the values of 1 A increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 gives the variation of f along with the distance from the plate. The variation of 1 A , the parameter which is associated with the viscosity function of the temperature produce a substantial change in a single valued function f of  . It is observed that the values of f increases sharply in magnitude as the values of 1 A increases.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the application in underground water resource and seepage of water under dam, Raptis et al [1] examined the free convection flow through a vertical porous media. In the other context Raptis et al [2,3] studied the similar problem by introducing mass transfer, constant suction and constant heat flux.…”
Section: Introductionmentioning
confidence: 99%
“…The flow through porous medium is very important particularly in the fields of agricultural engineering and technology for irrigation processes, especially in petroleum industry to study petroleum extraction process and transport, also in chemical engineering and technology for filtration and purification processes. A succession of explorations made by Raptis et al 1,2,3 into the study of two-dimensional flow through porous medium past an infinite vertical wall. Many authors [4][5][6][7][8][9] discussed an oscillatory three-dimensional flow through a porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Afifi [6] studied the aspects of a magneto-fluid with suspended particles. The fluid motion through a porous medium has been studied by many authors [7][8][9][10][11][12][13][14][15]. Tripathi [16,17] studied the influence of heat transfer in swallowing of food bolus (water) through the oesophagus and heat flow through porous finite channel.…”
Section: Introductionmentioning
confidence: 99%